Pembelajaran pengembangan kreativitas Senitari Sebagai upaya pembentukan karakter siswa Di SMK Mikael surakarta - Budi Setiyastuti (Institut Seni Indonesia Surakarta, 2016)
Learning as a process of interaction between student and teacher as well as source of learning at a created contion in oeder to develop behavior. Behavior developing is concerning conscious, continuous, positive and active developing and it is not tentative developing. Besides that, it also includes aspect of behavior and moreover, it has certain aim an direction. Creativity developing is an effort to attractively renovate in order to make it suited to the era and to be able to present artÂ as an effective media for creativity developing. It means that dance art which belongs to SMK Mikael becomes a media of growing and developing for dance â€œDancer Pom-pom boys Cheenicoâ€ that can be packed as dance spectacle communicated to the audience. The problem that will be analized in the process of dance learning includes how the process and way of dance appreciation learning for student in SMKMikael Surakarta are and what the methot used is. Dance learning has a function as self developing. It can give contribution to the studentâ€™ personal developing. The contribution include giving expression space, creative and imaginative developing, increasing the sense of self confidence, and developing cultural insight. For the reason, learning of art has special character and uniqueness. The approach used introduction, while the methods used to give theÂ materials are giving discourse, demontrating and drilling. Key words : learning, developing, creativity, and character.Â